2015
DOI: 10.1007/s12026-015-8631-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy study of lung cancer stem cell vaccine

Abstract: In this trial, lung cancer stem cells (CSCs) were separated and cultured to produce a vaccine; its safety and efficacy were prospectively evaluated in low-, medium-, and high-dose groups. Between February and September 2014, we enrolled 90 patients who met the enrollment criteria and assigned them to three groups (n = 30). Throughout the trial, injection site reaction was the most common reaction (63 %), and fever was least common (16 %); however, there was no difference among the three groups. When the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Despite the numerous immune-evasive properties of CSCs, preclinical studies that target them with immunotherapy have provided encouraging results, demonstrating that vaccines based on CSC lysates or dendritic cells (DC) that are loaded with CSCs are more effective than non-CSC-based equivalents in preventing tumor onset (28)(29)(30)(31)(32)(33)(34). Clinical trials using CSC-loaded DCs or CSC lysates have been performed on patients affected by different solid cancers, demonstrating that vaccination is safe and effectively induces a specific immune response (35)(36)(37). Lasting protection, with about 70% of patients still alive after 20 years, has been reported for AGI-101H, a vaccine that is comprised of irradiated melanoma cell lines engineered with hyper IL-6 (a fusion form of IL-6 and its soluble receptor) that grants it stem-like features (38).…”
Section: Cancer Stem Cell Immunologymentioning
confidence: 99%
“…Despite the numerous immune-evasive properties of CSCs, preclinical studies that target them with immunotherapy have provided encouraging results, demonstrating that vaccines based on CSC lysates or dendritic cells (DC) that are loaded with CSCs are more effective than non-CSC-based equivalents in preventing tumor onset (28)(29)(30)(31)(32)(33)(34). Clinical trials using CSC-loaded DCs or CSC lysates have been performed on patients affected by different solid cancers, demonstrating that vaccination is safe and effectively induces a specific immune response (35)(36)(37). Lasting protection, with about 70% of patients still alive after 20 years, has been reported for AGI-101H, a vaccine that is comprised of irradiated melanoma cell lines engineered with hyper IL-6 (a fusion form of IL-6 and its soluble receptor) that grants it stem-like features (38).…”
Section: Cancer Stem Cell Immunologymentioning
confidence: 99%
“…These encouraging results have led to the development of several clinical trials that use CSC lysates-or mRNA-loaded DC to vaccinate patients that bear ovarian, breast, lung, pancreatic, colorectal and liver cancers. The currently available results demonstrate that anti-CSC vaccination did not induce strong side effects, but that it elicited measurable and specific anti-tumor immune responses, thus proving its safety and suggesting that cancer patients may benefit from anti-CSC vaccination [33][34][35]. Despite the successes being reported in these clinical trials, it must be mentioned that DC-based vaccination presents many drawbacks; it is a cost-and time-consuming patient-specific treatment, and a great deal of effort is still required to standardize it.…”
Section: Csc Immunogenicitymentioning
confidence: 96%
“…Still, various studies have shown that CSCs could be immunogenic in certain settings. Currently, different clinical studies have been developed that use dendritic cells loaded with CSC or mRNA lysates to vaccinate patients with lung (116), pancreas (117), glioblastoma (118), and breast cancer (119) among others. The results showed that vaccination induces a measurable FIGURE 1 | (A) BCSCs could be eliminated through the immune response generated in situ when chemotherapy-sensitive tumor cells die from mechanisms such as immunogenic cell death.…”
Section: Evidence Of Immune Response Against Cancer Stem Cellsmentioning
confidence: 99%